Table 19 [videorecording (DVD)] - Blitz, Jeffrey, 1969-; Kendrick, Anna; Robinson, Craig, 1971-; Squibb, June, 1929-; Kudrow, Lisa (20th Century Fox Home Entertainment, 2017)
Ex-maid of honor Eloise, having been relieved of her duties after being unceremoniously dumped by the best man via text, decides to hold her head up high and attend her oldest friend's wedding anyway. She finds herself seated at the 'random' table in the back of the ballroom with a disparate group of strangers.